Common Mental Disorders and Substance Use in School Children of Eastern Nepal - Sharma, P; Sharma, P; Thakur, N; Sharma, S; Pokharel, M (Journal of Psychiatrists' Association of Nepal, 2019)
Introduction: School mental health is one of the important areas where early detection can lead to appropriate early intervention and burden of disease can be minimized. There is dearth of prevalence studies of common mental disorders on school going adolescents in Nepal. Considering this we aimed to study the prevalence of common mental health problems and substance use in school going adolescents. Material And Method: We evaluated 240 students for common mental disorders (depression and anxiety) using translated version of PHQ-4 and substance use single validated question after taking consent from school authorities and assent from students. Results: It was seen that 68.8 % students had psychological distress. 22.9 % and 27.5% of students had anxiety and depression respectively on screener and 23.3% students had use of substance at least once within a year. When compared male had significantly higher number of substance use as compared to female but no difference in PHQ-4 scores were seen when compared between gender and history of substance use. Conclusion: The study shows the current scenario of school going adolescents in Nepal and highlights the need of prevalence data on more generalizable setting.